A New Iron‐Based Carbon Monoxide Oxidation Catalyst: Structure–Activity Correlation. Issue 17 (11th September 2014) - Schoch, Roland; Huang, Heming; Schünemann, Volker; Bauer, Matthias
Abstract A new iron‐based catalyst for carbon monoxide oxidation, as a potential substitute for precious‐metal systems, has been prepared by using a facile impregnation method with iron tris‐acetylacetonate as a precursor on γ‐Al2O3. Light‐off and full conversion temperatures as low as 235 and 278 °C can be reached. However, the catalytic activity strongly depends on the loading; lower loadings perform better than higher ones. The different activities can be explained by variations of the structures formed. The structures are thoroughly characterized by a multimethodic approach by using X‐ray diffraction, Brunauer–Emmett–Teller surface areas, and Mössbauer spectroscopy combined with diffuse reflectance UV/Vis and X‐ray absorption spectroscopy. Consequently, isolated tetrahedrally coordinated Fe3+ centers and phases of AlFeO3 are identified as structural requirements for high activity in the oxidation of carbon monoxide.